2008
DOI: 10.1267/ahc.08025
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 Expression and Promoter Methylation of Cyclin D1 Gene Are Associated with Cyclin D1 Expression in Developing Rat Epididymal Duct

Abstract: Hypermethylation-dependent silencing of the gene is achieved by recruiting methyl-CpG binding proteins (MeCPs). Among the MeCPs, MeCP2 is the most abundantly and ubiquitously expressed in various types of cells. We first screened the distribution and expression pattern of MeCP2 in adult and developing rat tissues and found strong MeCP2 expression, albeit rather ubiquitously among normal tissues, in ganglion cells and intestinal epithelium in the small intestine, in Purkinje cells and neurons in the brain, in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We also showed that hMeCP2 expression in ECs can activate ISC activity. In mammals, MeCP2 was previously reported to regulate Cyclin D1 expression in developing rat gut (Darwanto et al, 2008), and it induces cell proliferation and growth of embryonic non-neuronal cells (Nagai et al, 2005) as well as prostate cancer cells (Bernard et al, 2006). Furthermore, MeCP2 has been reported to induce secretion of several growth factors such as brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1) and nerve growth factor (NGF) in the central nervous system (Schaevitz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that hMeCP2 expression in ECs can activate ISC activity. In mammals, MeCP2 was previously reported to regulate Cyclin D1 expression in developing rat gut (Darwanto et al, 2008), and it induces cell proliferation and growth of embryonic non-neuronal cells (Nagai et al, 2005) as well as prostate cancer cells (Bernard et al, 2006). Furthermore, MeCP2 has been reported to induce secretion of several growth factors such as brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1) and nerve growth factor (NGF) in the central nervous system (Schaevitz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of these in relation to gene expression was not investigated. Darwanto et al [54], however, showed an increase in the methylation of the CyclinD1 promoter during epididymal development, which appeared to be associated with a decreased expression of the gene. Nevertheless, the fact that DNA methylation may regulate the transcription of Panx1 may be important not only for epididymal function, but also in other tissues.…”
Section: Pannexin1 Promoter In the Epididymismentioning
confidence: 94%
“…15 However, recent studies using animal models have demonstrated that MeCP2 regulates the expression of a wide range of genes in the hypothalamus and may function as both an activator and a repressor of the target genes. 16 MeCP2 mRNA has been examined by in situ hybridization in rats and is shown to be expressed in the ganglion cells and intestinal epithelium of the small intestine, Purkinje cells and other neurons in the brain, and in cells of the testis, 19 In humans, expression is also found in the colonic mucosa and colon cancers. 20 Neuronal expression found in rats is similar to the immunohistochemical findings revealed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Selective neuronal staining was obtained in the cerebellar cortex and colonic Auerbach's plexus by taking into account that in rats MeCP2 mRNA expression is detected in these tissues and cells. 19 After incubation with the biotinylated second antibodies, immunoreactive products were either visualized by 3,3'-diaminobenzidine tetrahydrochloride (DAB) as brown, or by amino-ethyl carbazole (AEC) as red. For double immunolabeling, the sections were first incubated with an anti-large T monoclonal antibody which was visualized as blue by nitro-blue tetrazolium chloride/ 5-bromo-4-chloro-3'-indolylphosphatase (NBT/BCIP) via alkaline phosphatase reaction.…”
Section: Antibodiesmentioning
confidence: 99%